Analisis pendapatan pekebun kulit kayu manis (cassiavera) di Kecamatan Bukit Kerman, Kabupaten Kerinci (Studi Kasus Desa Pengasi Lama) - Inisa, Azura; Junaidi, Junaidi; Bhakti, Adi (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2024)
The aims of this study were to: 1) To analyze the socio-economic characteristics of cinnamon bark (cassiavera) smallholders in Pengasi Lama Village, Bukit Kerman District, Kerinci Regency. 2) To analyze the effect of land area, number of plants, price, and production costs on the income of cinnamon bark (cassiavera) smallholders in Pengasi Lama Village, Bukit Kerman District, Kerinci Regency. The data used are primary data and secondary data. The analytical method used in this research is descriptive analysis method with a quantitative approach and using multiple linear regression formulation. Based on the analysis of the socio-economic characteristics of cinnamon bark (cassiavera) planters in Pengasi Lama Village, it is dominated by planters with an average age of 31-38 years which are productive age, with the majority of respondents being male, namely 65 people. The average level of education of Cinnamon bark (cassiavera) planters is 39 people, the average family burden is 2-3 people, and the average income is IDR 301,728,000. Based on the results of the study, it was shown that the variable land area had a negative and insignificant effect on the income of cinnamon bark (cassiavera) planters, while the variable number of plants, price, and production costs had a positive and significant effect on the income of cinnamon bark (cassiavera) smallholders in Pengasi Lama Village.